Consumer preferences: product attributes determinants of honey consumption - Ribeiro, Maria Isabel (2018)
Honey is considered the only food of animal origin that can be consumed without being processed (Pocol and Teselios, 2012). The literature presents several reasons associated with the consumption of honey, namely, the fact of being a natural and healthy product; its dietary, nutritional and medicinal characteristics; the product quality; the geographical region of production; the information available on the products’ label, the brand's reputation; as well as the variety, texture, taste, aroma, appearance, packaging and price (Yeow et al., 2013; Wu et al., 2015). The present research intends to identify the intrinsic and extrinsic attributes of honey on which consumers base their purchasing decision.